2019
DOI: 10.3389/fmicb.2019.02085
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Analysis of the Mycoplasma bovis Genome Identified Non-essential, Adhesion- and Virulence-Related Genes

Abstract: Mycoplasma bovis is an important pathogen of cattle causing bovine mycoplasmosis. Clinical manifestations are numerous, but pneumonia, mastitis, and arthritis cases are mainly reported. Currently, no efficient vaccine is available and antibiotic treatments are not always satisfactory. The design of new, efficient prophylactic and therapeutic approaches requires a better understanding of the molecular mechanisms responsible for M. bovis pathogenicity. Random transposon mutagenesis has been widely used in Mycopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 88 publications
(169 reference statements)
1
17
0
Order By: Relevance
“…A more recent rlmD loss was observed for some species, including M. pulmonis, and subgroups of species including M. ovipneumoniae and M. hyopneumoniae (node 19). A recent gene-essentiality study based on transposon mutagenesis in M. bovis indicated that rlmD (MBOVJF4278_00748) was not necessary [67], reinforcing the dispensability of these rRNA methylases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent rlmD loss was observed for some species, including M. pulmonis, and subgroups of species including M. ovipneumoniae and M. hyopneumoniae (node 19). A recent gene-essentiality study based on transposon mutagenesis in M. bovis indicated that rlmD (MBOVJF4278_00748) was not necessary [67], reinforcing the dispensability of these rRNA methylases.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a transposon library of M. bovis strain JF-4278 was recently shown to include a trmFO-like disrupted mutant whose ability to bind to primary bovine mammary gland epithelial (bMec) cells was reduced, suggesting this gene is a virulence factor in M. bovis [67].…”
Section: Discussionmentioning
confidence: 99%
“…These laboratory conditions have largely contributed to the understanding of the biology of these minimal bacteria but provided only limited information on the strategies these organisms have evolved to secure their survival in the animal host and get access to essential nutritional resources. In the absence of small animal models, eukaryotic cell cultures as re-emerged as a valuable environment to revisit the minimal cell concept at the light of host-pathogen interactions [30][31][32][33]44]. Our functional genomic study with the genome-reduced pathogen M. bovis revealed that phosphodiesterases involved in cyclic dinucleotides and nanoRNAs degradation are critical for survival under cell culture conditions, while dispensable in axenic medium.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent rlmD loss was observed for some species, including M. pulmonis, and subgroups of species including M. ovipneumoniae and M. hyopneumoniae (node 19). A recent gene-essentiality study based on transposon mutagenesis in M. bovis indicated that rlmD (MBOVJF4278_00748) was not essential [67] reinforcing the dispensability of these rRNA methylases.…”
Section: Discussionmentioning
confidence: 99%
“…Their conclusion was mainly driven by the demonstration of a fibronectinbinding activity of TrmFO-like using ELISA and direct adhesion assays on embryonic bovine lung (EBL) cells, including inhibition by anti-TrmFO-like polyclonal antibiodies. In another study, a transposon library of M. bovis strain JF-4278 was recently shown to include a trmFO-like disrupted mutant which ability to bind to primary bovine mammary gland epithelial (bMec) cells was reduced, suggesting this gene is a virulence factor in M. bovis [67].…”
Section: Discussionmentioning
confidence: 99%